Mission: impossible. Ghost protocol [videorecording (Blu-Ray)] - Cruise, Tom, 1962-; Kapoor, Anil, 1959-; Renner, Jeremy (Paramount Home Entertainment, 2012)
Agent Ethan Hunt and his elite team go underground after a bombing of the Kremlin implicates the IMF (Impossible Mission Force) as international terrorists. While trying to clear the agency's name, the team uncovers a plot to start a nuclear war. Now, to save the world, they must use every high-tech trick in the book.--Container.